Russia's War Against Ukraine - Sasse, Gwendolyn, 1972- (Polity, 2023)
"On 24 February 2022, Russia launched a full-scale invasion of Ukraine, giving rise to the deadliest conflict on European soil since the Second World War. How could this happen in twenty-first-century Europe? Why did Putin decide to escalate Russia's war against Ukraine, a war which began with Russia's annexation of Crimea in 2014? In this timely book, Gwendolyn Sasse analyses the background to this war and examines the factors that led to Putin's fateful decision. She retraces the history of Ukraine's struggle for independence from Russia and shows how democratic developments in Ukraine had become a risk for Russia's political system. She also shows that ambiguous Western policy towards Russia encouraged elites in the Kremlin to think that they had more room for action than they did. The result is a brilliant analysis of the background to the war, a concise account of the course of the war itself and a timely reflection on what its consequences will be - for Ukraine, for Russia and for the West. An indispensable book for anyone who wants to understand the most dangerous conflict of our time"--Amazon